The Influence of ESG on Return on Asset ASEAN Companies 2013-2023 - Masditok, Tokit; Gunarsih, Tri; Geraldina, Ira; Wihadanto, Ake (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2024)
In the last few decades, sustainability issues have received increasing attention among stakeholders in their business operations. Although many studies have examined the influence of ESG on the financial performance of companies in various regions, specific research that focuses on companies in ASEAN is still limited. Studies that directly link each Pillar Score and ESG Combine Score with ROA are still rare. This research offers a new contribution by providing a comprehensive analysis of the influence of each ESG pillar and ESG Combine Score on ROA in the ASEAN region. This research aims to analyze the influence of the Environmental Pillar Score, Social Pillar Score, Governance Pillar Score, and ESG Combined Score on ROA in ASEAN public companies 2013-2023. The research uses a quantitative approach with multiple linear regression analysis to evaluate the relationship between ESG scores and ROA. The research results show that each Pillar Score and ESG Combine Score have a significant positive effect on ROA. The research results provide the implication that companies need to increase their focus on sustainable practices to improve financial performance. Investors can use it as a reference for considering ESG scores in investment decisions. This research cannot be generalized to different regions or periods and is limited to several public companies and the research time range 2013-2023. External factors such as government policies and macroeconomic conditions can also influence research results.